2020
DOI: 10.4103/jpbs.jpbs_150_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fracture resistance and color stability of crowns obtained by layering composite over zirconia and polyetheretherketone copings before and after thermocycling to simulate oral environment: An in vitro study

Abstract: A BSTRACT Background: Most common material used for the fabrication of an implant restoration is full-ceramic crown or an all-ceramic crown. Frequent chipping of the ceramic under occlusal load has posed a great problem to the clinician and the patient. Composites have been layered over zirconia successfully in the recent past to overcome this problem. This study, thus, aimed to evaluate and compare the fracture resistance and color stability of crowns obtained by layeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…To evaluate the color stability of restorative material in simulation with an oral environment, a study was conducted on zirconia and PEEK copings veneered with an indirect composite under thermocycle and concluded that shades of the crowns have been affected by thermocycling, which is not in correlation with our study [7]. Various studies were conducted on the color stability of feldspathic porcelain and zirconia under different exposures of oral simulations and proved that these effects were higher on natural teeth and zirconia with feldspathic porcelain as least affected [11,12].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…To evaluate the color stability of restorative material in simulation with an oral environment, a study was conducted on zirconia and PEEK copings veneered with an indirect composite under thermocycle and concluded that shades of the crowns have been affected by thermocycling, which is not in correlation with our study [7]. Various studies were conducted on the color stability of feldspathic porcelain and zirconia under different exposures of oral simulations and proved that these effects were higher on natural teeth and zirconia with feldspathic porcelain as least affected [11,12].…”
Section: Discussioncontrasting
confidence: 60%
“…The Zirconia (CaroZiir S, UK) was then sintered at 1450°C for 60 minutes. The Zirconia copings were layered with feldspathic porcelain (Ivoclar Emax, Ivoclar Vivaden, US), and PEEK crowns were layered with indirect composite (Bredent), which were then polished with polishing paste and rubber wheel according to the manufacturer's protocol [6,7]. A putty template was taken before the tooth preparations, and the same template was used to veneer porcelain and indirect composite over the samples to eliminate any bias toward the thickness of the veneer and maintenance of its natural anatomy.…”
Section: Sample Preparationmentioning
confidence: 99%
“…We understand that the clinical indications of PEK and PEEK materials used presently are very limited-they can be applied clinically as a core design and must be covered by composite resin for esthetic reasons. 36 The purpose of the present study was not to simulate the clinical oral environment, as the CTC test does not consistently result in clinically observed failures. The values for the flexural strength and fracture loads for the bar and disc specimens used presently were published elsewhere, with the current focus being qualitative assessment of fracture surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The crowns were not exposed to artificial aging (thermocycling) to make the study more clinically relevant and to be consistent with the bar specimens, for which thermocycling is not recommended by the ISO standard for testing flexural strength. We understand that the clinical indications of PEK and PEEK materials used presently are very limited—they can be applied clinically as a core design and must be covered by composite resin for esthetic reasons 36 . The purpose of the present study was not to simulate the clinical oral environment, as the CTC test does not consistently result in clinically observed failures.…”
Section: Discussionmentioning
confidence: 99%
“…PEEK is manufactured through computer-aided design and computer-aided manufacturing (CAD/CAM) technology, while PEKK may also be heat-pressed [9]. PEEK was initially applied to frameworks for fixed partial dentures [10][11][12] and removable partial dentures [13], implant abutments [14,15], surgical membranes [16], post cores [17], and implant bodies [18].…”
Section: Introductionmentioning
confidence: 99%